OP0182 A Pharmacometric-Based Analysis Indicated NO Relationship between Occurrence of Safety Events and Canakinumab Exposure in Systemic Juvenile Idiopathic Arthritis Patients. (10th June 2014) - Dumortier, T.; Ruperto, N.; Brunner, H.I.; Luttringer, O.
Abstract : Background: Canakinumab, a fully human, selective anti-interleukin-1β (IL-1β) monoclonal antibody, has demonstrated rapid and sustained efficacy in systemic juvenile idiopathic arthritis (SJIA) patients, 1 and is approved in >30 countries including USA, EU, Canada, UK and Russia. Given the nature of the disease (pediatric population, rare condition), the phase 3 program only included limited placebo data. In such a context, the safety profile of canakinumab has been characterized via a model-based analysis of the dose-exposure-safety event relationship. Objectives: To explore the relationship between canakinumab concentration and the occurrence of AEs of interest and clinically meaningful lab abnormalities. Methods: The analysis considered the first portion of the phase III trial where SJIA patients received canakinumab 4mg/kg (300 mg max.) every 4 weeks for a maximum of 8 consecutive doses (n=188). Individual canakinumab concentration time-profiles have been predicted for those patients, by combining the patients' canakinumab and IL-1β concentration-time data and an established population PK model. This model is a PK-binding model parameterized in terms of clearance of drug and ligand (IL-1β), central and peripheral volume for the drug, interstitial flow rate, ligand production rate and binding affinity which has been developed using all the data available from the entire canakinumab program. The average serum canakinumab concentration (Cavg) was calculated from the concentration time profiles for each patient and dosing interval. In each dosing interval, Cavg were compared between patients with and without the following safety events of interest: AEs of abdominal pain, cough, headache, infection, serious AE infection, pyrexia, and vomiting, as well as lab abnormalities of thrombocytopenia (>3XULN [upper limit normal]), leukopenia (≤0.8 XLLN [lower limit normal]), >20g/L decrease from baseline hemoglobin, neutropenia (<0.9 X LLN), transaminases elevation (>3XLLN), elevated total cholesterol (≥1.5XULN), triglycerides (≥5.7 mmol/L), and ≥25% decrease from baseline estimated glomerular filtration rate for 2 consecutive visits. Results: For all AEs and lab abnormalities, except neutropenia, Cavg was not different for patients who experienced an event compared with those who did not. The mean Cavg for patients with neutropenia was comparable to the 74th percentile of those patients without neutropenia, however this higher Cavg was not found to be associated with more infection. Conclusions: A pharmacometric based analysis in SJIA patients treated with a therapeutic dose of canakinumab, did not find, in the range of canakinumab exposure observed, any relationship between average canakinumab exposure and the occurrence of any specific safety events, except for neutropenia. This increased Cavg in patients with neutropenia was not associated with increased infections. These data support the effective and safe use of canakinumab 4mg/kg every 4 week for the treatment of SJIA in patients >2 years old. References: Ruperto N. et al. N Engl J Med 2012;367 (25):2396-406. Disclosure of Interest: T. Dumortier Shareholder of: Novartis, Employee of: Novartis, N. Ruperto Grant/research support: Gaslini Hospital: Abbott, Astrazeneca, BMS, Centocor Research & Development, Eli Lilly and Company, "Francesco Angelini", Glaxo Smith & Kline, Italfarmaco, Novartis, Pfizer Inc., Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers bureau: Astrazeneca, Bristol Myers and Squibb, Janssen Biologics B.V., Roche, Wyeth/Pfizer, H. Brunner Consultant for: Novarits, Roche, Astrazeneca, Celgene, Pfizer, Janssen, UCB, GSK, BMS, Speakers bureau: Novartis, O. Luttringer Employee of: Novartis DOI: 10.1136/annrheumdis-2014-eular.4016